Stadїї včinenn zločinu v ukraїns′kij doktrinì krimìnal′nogo prava : ponâttâ ta vidi - Burdìn, Volodimir (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The problematic issues of the notion of stages of committing a crime are analyzed. These stages should be considered as outwardly expressed stages of criminal intent realization. The provision on the necessity of criminal consequences of each concrete stage of committing a crime proved disputable.
Keywords: ukraiński kodeks karny; przestępstwo; doktryna prawa karnego; pojęcie przestępstwa; rodzaje przestępstw